Ultrastructure of the rotifer integument: peculiarities of Sinantherina socialis (Monogononta: Gnesiotrocha). Issue 3 (6th May 2015) - Hochberg, Rick; Hochberg, Adele; Chan, Courtney
Abstract The rotifer integument is a well‐described syncytium that contains an apical intracytoplasmic lamina (ICL) that functions for both skeletal support and muscle insertion. To date, there is limited information on the structure of the integument in species of Gnesiotrocha, a diverse subclade of Monogononta that consists of solitary, colonial, sessile, and planktonic species. In this study, we examined the ultrastructure of the integument in the colonial rotifer Sinantherina socialis to determine how it corresponds to that of other monogononts. The integument of S. socialis was broadly similar to that of other rotifers, consisting of a thickened glycocalyx, multilaminate ICL, and syncytial epidermis. However, it was different in several regards. The ICL consisted of three distinct layers from apical to basal: layer 1 consisted of at least two electron‐dense laminae; layer 2 was a thickened matrix of amorphous, electron‐dense material or was fibrous; and layer 3 was an electron‐dense lamina of varying thickness that covered the underlying syncytium. Significantly, layers 1 and 2 formed a ridge‐and‐groove like system of finger‐like projections across the trunk surface that has not been observed in other rotifers. A voluminous syncytial cytoplasm (up to 3 μm thick) was present beneath the ICL and was mostly electron lucent and with few organelles. Bundles of potential microtubules were scattered throughout the syncytium. We hypothesize that the voluminous cytoplasm with microtubules serves as skeletal support for the rotifer's sessile lifestyle, while the external ridges may function as a texture‐based deterrent to predators, or serves to trap secretions from the species' defensive glands. Basally, the epidermis was highly folded and bordered by a thin basal lamina that separated the plasmalemma from the blastocoel. Membrane‐bound vesicles were present throughout the integument's cytoplasm and are hypothesized to function in the secretion of extracellular matrix and in the maintenance of the ICL.